Orexin A presynaptically decreases inhibitory synaptic transmission in rat locus coeruleus neurons. (14th September 2018) - Kargar, Hossein Mohammad-Pour; Azizi, Hossein; Mirnajafi-Zadeh, Javad; Mani, Ali Reza; Semnanian, Saeed
Highlights: Orexin A via OX1 receptors decreased eIPSCs amplitude in LC neurons. Orexin A decreased eIPSCs amplitude via intracellular Ca 2+ level and PLC activation. Orexin A increased PPR and sIPSCs frequency but had no effect on sIPSCs Amplitude. Endocannabinoid CB1 receptors mediate orexin A effects in the LC neurons. Abstract: Locus coeruleus nucleus (LC) is a major noradrenergic nucleus in the brain. It receives dense orexinergic projections from lateral hypothalamus. Whilst it is known that orexin A increases firing rate of LC neurons, its effect on spontaneous and evoked inhibitory postsynaptic currents (sIPSCs and eIPSCs, respectively) has not been yet identified. In this research, we investigated the effect of orexin A on eIPSCs and sIPSCs in LC neurons. Whole-cell recordings revealed that orexin A suppresses eIPSCs amplitude in which this effect was blocked by an orexin type-1 receptors antagonist (SB-334867) and cannabinoid type-1 (CB1) receptors antagonist (AM251). Moreover, exposure of neurons to BAPTA (Ca 2+ chelator) and U73122 (phospholipase C inhibitor) prevented orexin A-induced eIPSCs depression. On the other hand, orexin A increased pair pulse ratio and sIPSCs frequency but had no effect on sIPSCs amplitude. Our results revealed that eIPSCs suppression in the LC is mediated by CB1 receptor through a presynaptic mechanism.